Crime 101 [videorecording (Blu-Ray)] - Blanck Mass (Musician) (Amazon MGM Studios, 2026)
"When an elusive jewel thief eyes the score of a lifetime, his path crosses that of a disillusioned insurance broker who is facing her own crossroads. Convinced he has found a pattern a relentless detective is closing in, raising the stakes even higher. As the heist approaches, the line between hunter and hunted begins to blur, and all three are faced with life-defining choices--and the realization that there can be no turning back."--